Islamic Education Management perspective of Noah AS - Bachtiar Hariyadi (EDUTEC : Journal of Education And Technology, 2018)
This study aims to explain the implementation of the wisdom of Idariyah in the management of Islamic education. This research is a literature study. Data collection methods used are studies taken from books that discuss Noah and management of Islamic education. The results of this study are Islamic education is an organization based on the Qur'an and the hadith of the Prophet, so the management must be absolutely perfect in all aspects. Noah was a model of an outstanding leader in dealing with the problems of his people, firmly defending the truth, never giving up and not caring about demons who discouraged his preaching. His perseverance and determination must be set as an example by today's leaders.